A Comprehensive Systematic Review of The Relationship between Vaginal Douching and The Increased Risk of Bacterial Vaginosis and Sexually Transmitted Infections - Annisa Nurul Qalbi; Andaru Cahya Sekarini (International Medical Journal Corp. Ltd, 2025)
Introduction: Vaginal douching is a widespread intimate hygiene practice, particularly among women of reproductive age, driven by cultural, religious, and personal hygiene motivations. Despite its prevalence, there is ongoing debate regarding its impact on vaginal health, specifically its potential role in increasing the risk of Bacterial Vaginosis (BV) and Sexually Transmitted Infections (STIs) (Rael et al., 2021; Umami et al., 2022). Methods: This comprehensive systematic review followed a structured screening and data extraction protocol. We included observational studies (cohort, case-control, cross-sectional) and systematic reviews/meta-analyses examining vaginal douching as a primary exposure and reporting BV and/or STI outcomes. A total of 40 sources were included after applying criteria related to population, exposure, outcomes, and study design. Results: The evidence presents a complex and heterogeneous picture. For BV, intervention studies on douching cessation showed minimal overall impact on prevalence (Klebanoff et al., 2006; Sivapalasingam et al., 2014; Masese et al., 2012). However, subgroup analyses revealed significant risk reduction for women who douched post-menstruation (Brotman et al., 2008). Observational data indicated an increased risk of BV recurrence associated with vaginal cleansing (Guédou et al., 2013). For STIs, findings were inconsistent. While a large RCT found no significant link between douching and Pelvic Inflammatory Disease (PID) (Rothman et al., 2003), meta-analyses suggested an elevated risk of HIV acquisition (Hilber et al., 2010; Low et al., 2011), and cross-sectional studies reported higher STD history among douchers (Yıldırım et al., 2020). Dose-response relationships were noted for HPV infection (Museba et al., 2021). Discussion: The heterogeneity in findings can be attributed to population differences, methodological quality, douching practices (frequency, timing, solution), and challenges with reverse causation and confounding. Biological mechanisms proposed include disruption of vaginal microbiota and pH, mucosal trauma, and inflammation (Sivapalasingam et al., 2014; Tokmak et al., 2015; Masese et al., 2011). Conclusion: Current evidence does not support a universal, strong causal link between all douching practices and increased BV/STI risk. The association appears modified by practice characteristics and population context. Public health messaging should move beyond blanket warnings to provide nuanced, context-specific education on vaginal health.